Analyzing the Impact of Plyometric Training on Motor Fitness and Physiological Parameters in Kabaddi Players - Manjunath Sajjan (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Plyometric training (PT), a high-intensity training (HIT) approach involving jumps, sprints, and fast directional changes is highly appreciated sport-specific training owing to its positive impact in improving neuromuscular adaptations including action repetitions with biomechanical specificity and targeting: maximal force, rapid force, and jerk needed during the rapid acceleration, dynamic stability, and peak force production while performing raids and counter-attacks during gameplay for Kabaddi players, this paper which is a narrative review based on the analysis of secondary data sources discusses the mechanisms of PT on motor fitness components such as Speed, Agility, Balance, Coordination, and Strengths and its effects on physiological parameters like VO₂ max, anaerobic capacity, and lactate threshold, existing literature observes structured PF program offers significant improvement in leg explosive strength, reaction time, and cardiovascular endurance thus optimizing overall match performance while the improved proprioceptive strength of ligaments around joints challenged by physical activity postulates to reduce chances of injury, findings further suggest PT should be administered in combination with sport-specific drills for 8 to 12 weeks for reliable improvements in explosive strength with metabolic economy, as sports science sensu focuses on concomitant neuromuscular adaptations for a competitive edge, ultimately integrating PT in Kabaddi (game-specific) training protocols promotes a global level of athleticism, lowers fatigue-induced performance decrement, and improves game-specific ability, so their the scientific integration of PT becomes a basic norm for modern player development and competitive achievement in Kabaddi.